A conduta psicossocial subjetiva dos empresários e a opção pela exportação: um estudo do setor moveleiro de Arapongas - PR - Rambalducci, Marcos Jerônimo Goroski (2009)
All research up to now aimed at identifying the reasons for the low participation of Brazilian industry in international trade does not handle us the answer why some companies choose to export while others do not, even though geographically laid next to each other, manufacturing similar products, and subject to the same environmental conditions. This gap may result from an underestimation of the importance of human subjectivity in its social context in making decisions that affect the o organization. This research was conducted along the lines of symbolic interactionism and followed the methodological procedures of Grounded Theory. The data were collected through 18 interviews with 12 entrepreneurs in the industry, and were analyzed with the help of the software ATLAS/ti. Entrepreneurs who had export conduct were those who own the company as an instrument to achieve economic, social, and self rewards. The entrepreneurs who did not present export conduct were those who own the company only as a tool for economic reward. For these, the company is not the result of a vocational option, but rather a means by which one gets financial security for oneself and one s own, or even it serves as a substitute to the failure of one's financial or professional aspirations. Moreover, it was possible to identify differences in conduct among exporters which are associated with the different subjective psychosocial behavior of the entrepreneurs, and it was possible to group them into four profiles: grouped proactive, independent proactive, independent reactive, and grouped reactive.